2010
DOI: 10.1093/molbev/msq079
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Analyses Reveal Little Evidence for Adaptive Evolution in Many Plant Species

Abstract: The relative contribution of advantageous and neutral mutations to the evolutionary process is a central problem in evolutionary biology. Current estimates suggest that whereas Drosophila, mice, and bacteria have undergone extensive adaptive evolution, hominids show little or no evidence of adaptive evolution in protein-coding sequences. This may be a consequence of differences in effective population size. To study the matter further, we have investigated whether plants show evidence of adaptive evolution usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
281
4
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(332 citation statements)
references
References 77 publications
37
281
4
1
Order By: Relevance
“…Under population structure, mutations responsible for local adaptation are not considered in species-wide measures of fixed adaptive substitutions. Strong spatial structuring is thus suggested to explain the lack of positive selection found by Gossmann et al (2010) in various plant species, in contrast to results in Capsella grandiflora, a species with low population subdivision that appears to exhibit high rates of adaptive substitutions (a ¼ 40%; Slotte et al, 2010).…”
Section: Selection In Coding Regionsmentioning
confidence: 65%
See 3 more Smart Citations
“…Under population structure, mutations responsible for local adaptation are not considered in species-wide measures of fixed adaptive substitutions. Strong spatial structuring is thus suggested to explain the lack of positive selection found by Gossmann et al (2010) in various plant species, in contrast to results in Capsella grandiflora, a species with low population subdivision that appears to exhibit high rates of adaptive substitutions (a ¼ 40%; Slotte et al, 2010).…”
Section: Selection In Coding Regionsmentioning
confidence: 65%
“…These loci are housekeeping genes, chosen because they are conserved among species , and thus it is unsurprising that they exhibit high levels of purifying selection in coding regions for maintaining their functions. Strong purifying selection was also found in coding regions of other plant species (Gossmann et al, 2010;Slotte et al, 2010).…”
Section: Selection In Coding Regionsmentioning
confidence: 88%
See 2 more Smart Citations
“…Several recent studies have investigated evidence for adaptation in plant genomes (Gossman et al 2010), including specifically on the flowering-time gene network (Flowers et al 2009, Hall et al 2011, and have found scant evidence for adaptive evolution (but see Ingvarsson 2010and Hall et al 2011for Populus, and Slotte et al 2010 for Capsella). However, the generally employed sampling schemes and analytical methods in these and similar studies are designed to detect positive selection on a species-wide scale, and less attention has been paid to scanning sequence data for signatures of local selection within a species (Tenaillon and Tiffin 2008;Siol et al 2010).…”
Section: Molecular Adaptation Of Phenology Network Genesmentioning
confidence: 99%